Characterization of angularly resolved EUV emission from 2-µm-wavelength laser-driven Sn plasmas using preformed liquid disk targets. (28th June 2021) - Schupp, R; Behnke, L; Bouza, Z; Mazzotta, Z; Mostafa, Y; Lassise, A; Poirier, L; Sheil, J; Bayraktar, M; Ubachs, W; Hoekstra, R; Versolato, O O
Abstract: The emission properties of tin plasmas, produced by the irradiation of preformed liquid tin targets by several-ns-long 2 µ m-wavelength laser pulses, are studied in the extreme ultraviolet (EUV) regime. In a two-pulse scheme, a pre-pulse laser is first used to deform tin microdroplets into thin, extended disks before the main (2 µ m) pulse creates the EUV-emitting plasma. Irradiating 30- to 300 µ m-diameter targets with 2 µ m laser pulses, we find that the efficiency in creating EUV light around 13.5 nm follows the fraction of laser light that overlaps with the target. Next, the effects of a change in 2 µ m drive laser intensity (0.6–1.8 × 10 11 W cm −2 ) and pulse duration (3.7–7.4 ns) are studied. It is found that the angular dependence of the emission of light within a 2% bandwidth around 13.5 nm and within the backward 2 π hemisphere around the incoming laser beam is almost independent of intensity and duration of the 2 µ m drive laser. With increasing target diameter, the emission in this 2% bandwidth becomes increasingly anisotropic, with a greater fraction of light being emitted into the hemisphere of the incoming laser beam. For direct comparison, a similar set of experiments is performed with a 1 µ m-wavelength drive laser. Emission spectra, recorded in a 5.5–25.5 nm wavelength range, show significant self-absorption of light around 13.5 nm in the 1 µ m case, while in the 2 µ m case only an opacity-related broadening of the spectral feature at 13.5 nm is observed. This work demonstrates the enhanced capabilities and performance of 2 µ m-driven plasmas produced from disk targets when compared to 1 µ m-driven plasmas, providing strong motivation for the use of 2 µ m lasers as drive lasers in future high-power sources of EUV light.